(untitled) (Agroindustria, Sociedad y Ambiente, 2016)
Management refers to the organizations that carry out activities of planning, organization, direction and control in order to use its human, physical and financial resources in order to achieve objectives. When organizations assume the active participation of its employees as a common practice in the development of its normal activities, making fundamental pillar of its institutional success, are assuming an attitude of learning and improve in a participatory manner. The staff, in this case, the feel is motivated and identified with the service that provides, manages to meet the expectations of the customer thus improving the efficiency of the Organization, offering products and services of quality. In the case of virtual organizations, human talent must have greater motivation and strategies for active participation in the processes that develop this organization.